2013
DOI: 10.1590/s1679-78252013000200008
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and Mathematical Modeling and Optimization of Fiber Metal Laminates (FMLs) subjected to low-velocity impact via combined response surface regression and zero-One programming

Abstract: This paper presents analytical and mathematical modeling and optimization of the dynamic behavior of the fiber metal laminates (FMLs) subjected to low-velocity impact. The deflection to thickness (w/h) ratio has been identified through the governing equations of the plate that are solved using the first-order shear deformation theory as well as the Fourier series method. With the help of a two degrees-of-freedom system, consisting of springs-masses, and the Choi's linearized Hertzian contact model the interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…This agreed with the findings of an analytical study carried out by Ghasemi. 11 The results also showed that the position of the metal/composite plies significantly affected the impact property. The best impact property was obtained from specimens with metallic outer plies.…”
Section: Introductionmentioning
confidence: 90%
“…This agreed with the findings of an analytical study carried out by Ghasemi. 11 The results also showed that the position of the metal/composite plies significantly affected the impact property. The best impact property was obtained from specimens with metallic outer plies.…”
Section: Introductionmentioning
confidence: 90%
“…This was used for the estimation of the deflection ratio, which was a mathematical function of the main process planning parameters. Ghasemi et al (2013) optimized the process parameters for fibre metal laminates to a low velocity impact using response surface methodology and zero-one programming. It has been found that layer sequences and volume fractions of Al plies play significant role in the behaviour of fibre metal laminates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In literature, few studies are presented with the aim to optimize the FML configuration for given performance. What characterizes all of them is that they relate to optimization for a single specific condition, like vibration and damping characteristics or impact resistance . None of these studies considers the combination of multiple constraints related to different properties.…”
Section: Introductionmentioning
confidence: 99%